Survey of braid-based cryptography - ZHU Ping1; WEN Qiao-yan2 (Tongxin xuebao)
The achievements of braid-based cryptography were surveyed: some recently developed cryptographic schemes were introduced, including key exchange protocols enciphering-deciphering and authentication schemes. The attacks against these schemes were reviewed, such as solutions to conjugacy problems, length-based attacks, and linear representation-based attacks. Some problems in the study of this field were discussed, and several hints for future work were pointed out as well.